Advantage of zinc oxide nanoparticles over silver nanoparticles for the management of Aeromonas veronii infection in Xiphophorus hellerii. (October 2020) - Das, Soumya; Aswani, R.; Midhun, Sebastian Jose; Radhakrishnan, E.K.; Mathew, Jyothis
Abstract: Bacterial pathogens cause significant challenge to the ornamental fish industry. Eventhough antibiotic administration has been recommended to manage fish diseases, there is alarming concern with emergence of antibiotic resistance. This indicates the need for the development of alternative methods with multi-targeted action to manage fish diseases. In the study, silver (AgNPs) and zinc oxide (ZnONPs) nanoparticles have been evaluated for its activity against Aeromonas veronii . Both the AgNPs and ZnONPs were found to have bactericidal activity against A. veronii . In vivo experiments with A. veronii was found to cause severe mortality in Xiphophorus hellerii with a LD50 of 1.4 × 10 8 CFU/mL. However, treatment with AgNPs and ZnONPs each at a concentration of 1 mg/L was found to enhance the survival rate of X. hellerii to 83.3% and 100% respectively. Further histopathological analysis showed alterations in gill, intestine and liver of X. hellerii due to A. veronii in the infection control. In the case of AgNPs treated group, symptoms of moderate tissue damage could be observed. However, the ZnONPs treated X. hellerii showed normal histological features with minimum tissue damage. The bath dip method further confirmed the protective ability of the zinc oxide nanoparticles (1 mg/L) on X. hellerii . Highlights: Antimicrobial effectiveness of silver nanoparticles (AgNPs) against the fish pathogen A. veronii . Antimicrobial activity of zinc oxide nanoparticles (ZnONPs) against A. veronii . Application of nanoparticles to protect X. hellerii from A. veronii mediated infection. ZnONPs as superior nano-therapeutic in X. hellerii over AgNPs.